HALYMENIACEAE FAMILY (HALYMENIALES, RHODOPHYTA), NEW RECORDS ON THE COAST OF ALAGOAS, BRAZIL - Coelho, Élica Amara Cecilia Guedes (2022)
The Halymeniaceae family (Halymeniales, Rhodophyta) has great ecological importance as primary producers, economic and medical bioactive compounds. In the State of Alagoas, studies on this family are still scarce and the present work aimed to identify, describe and provide information on the diversity and ecology of the species of Halymeniaceae on the coast of Alagoas. The collections were performed in the intertidal region of the beaches: Sonho Verde, Mirante da Sereia, Riacho Doce (northern coast), Pajuçara (central coast) and Pontal do Coruripe (southern coast), during the dry season (September and October 2017 / March and September 2018) and rain season (April, May, July and August 2018). Halymeniaceae voucher species deposited in the ficological collection of the MAC Herbarium of the Alagoas Environment Institute were also analysed. Most samples were collected growing on rocky substrate encrusted by coralline and/or coral. H. clathrata E.C. Oliveira, F. Pinheiro-Vieira & R.E Norris and Grateloupia cf. filicina (J.V. Lamouroux) C. Agardh are new registration for the Alagoas coast and had its geographical distribution enlarged.